2022
DOI: 10.3390/cancers14133235
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cost-Effectiveness of the Comprehensive Geriatric Assessment in Geriatric Oncology: A Narrative Review

Abstract: The Comprehensive Geriatric Assessment (CGA) and the corresponding geriatric interventions are beneficial for community-dwelling older persons in terms of reduced mortality, disability, institutionalisation and healthcare utilisation. However, the value of CGA in the management of older cancer patients both in terms of clinical outcomes and in cost-effectiveness remains to be fully established, and CGA is still far from being routinely implemented in geriatric oncology. This narrative review aims to analyse th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…In recent years, the concept of being elderly has changed from a purely chronological evaluation to a more complex one, which also considers the biological age and functional and social status of the subjects. In this regard, several scales have been developed that can assess specific aspects, including function, comorbidities, quality of life, cognition, and emotional state [ 31 ], and a comprehensive geriatric assessment on decision making and treatment allocation is usually included in the multidisciplinary evaluation of elderly NSCLC patients.…”
Section: Io In Elderly Nsclc Patientsmentioning
confidence: 99%
“…In recent years, the concept of being elderly has changed from a purely chronological evaluation to a more complex one, which also considers the biological age and functional and social status of the subjects. In this regard, several scales have been developed that can assess specific aspects, including function, comorbidities, quality of life, cognition, and emotional state [ 31 ], and a comprehensive geriatric assessment on decision making and treatment allocation is usually included in the multidisciplinary evaluation of elderly NSCLC patients.…”
Section: Io In Elderly Nsclc Patientsmentioning
confidence: 99%
“…Further, it is arguable that the implementation of such a RTT role has the potential to be cost neutral and could potentially encompass specialisation in care of the older adult more broadly across the cancer care pathway [43] . Analyses to date lean toward a positive cost-effectiveness of geriatric focussed interventions in clinical practice in cancer [46] . We argue this would likely to translate into RO in terms of cost and staff resource savings via reduction of in-hospital admissions/length of stay, RT treatment toxicity and completion.…”
Section: Rtt and Older Adults With Cancermentioning
confidence: 99%
“…management of impairments identified by a systematic assessment of comorbidities, medications, nutritional status, physical and cognitive function, depressive symptoms, and social support [ 7 , 8 , 9 ]. Several randomised controlled trials (RCT), predominantly addressing older patients receiving cancer surgery or chemotherapy, have shown that GAM interventions may facilitate treatment completion, and reduce adverse events and the need for hospital services [ 10 , 11 ]. Benefits related to quality of life (QoL) and physical performance are more poorly documented [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%